Economic Empowerment of Coffee Farmers Through Dompet Dhuafa's Social Enterprise Program - Umaima; Muh. Yusuf; Mukhtar Yunus; Muhammad Jabbarul Qubra (Universitas Islam Negeri Alauddin Makassar, 2024)
The empowerment of coffee farmer groups by Dompet Dhuafa aims to improve the welfare and income of farmers in Letta Village, Lembang District, Pinrang Regency through a social enterprise program. This research uses a descriptive qualitative method to explore field facts related to the implementation of the program. The results show the pattern of implementing a social enterprise program that prioritizes elements such as social values, civil society, innovation, and economic activity. Dompet Dhuafa provides a coffee roaster machine for the business partner, warkop Gudmud, with funding from ZISWAF, and the profits obtained are used to provide sustainable social impact for the community.